STRATEGI KOMANDO RESOR MILITER 043/ GARUDA HITAM DALAM PENANGGULANGAN BENCANA ALAM DI PROPINSI LAMPUNG - Priambodo, Agung; Widyaningrum, Nrangwesthi; Rahmat, Hayatul Khairul (Universitas Medan Area, 2020)
The role of the Military Resort Command in disaster management is a form of implementation of the Indonesian Armed Forces? tasks, namely the task of Military Operations Other Than War (OMSP) in accordance with the mandate of Law Number 32 of 2004 concerning the Indonesian Armed Forces (TNI). Disaster management in the regions carried out by the the Military Resort Command involvement of government agencies and other stakeholders. Between the the Military Resort Command, government agencies and stakeholders in disaster management. Related to the role of the the Military Resort Command, this research was conducted with the aim to study the the Military Resort Command 043/ Garuda Hitam?s Strategy for disaster management in Lampung Province. This research uses a qualitative method using case studies. In addition, researchers conducted interviews, observations and documentation studies to collect data and analyzed. The Military Resort Command 043/ Garuda Hitam in disaster management is by coordinating and communicating with government agencies and other stakeholders as well as facilitating Territorial Development (Binter) activities which are one of the tasks of the Military Resort Command 043/ Garuda Hitam in Lampung Province.